Takhrij and Syarah Hadith of Agrotechnology: Utilization of Inai and Katam Leaves to Shine Hair - Dias Anggraeta; H. M. Subandi; Wahyudin Darmalaksana (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the hadith with regard to agrotechnology. This research method is a qualitative type through literature and field studies with the takhrij and syarah hadith approaches. The results and discussion of this research is the use of Inai and Katam leaves. The conclusion of this research is takhrij and syarah hadith about dyeing hair by utilizing Inai and Katam plants so as not to cause side effects on hair.